2012
DOI: 10.1039/c1nr11191d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multi-level carbon nanotube arrays with adjustable patterns

Abstract: Multi-level carbon nanotube (CNT) arrays with adjustable patterns were prepared by a combination of the breath figure (BF) process and chemical vapor deposition. Polystyrene-b-poly(acrylic acid)/ferrocene was dissolved in carbon disulfide and cast onto a Si substrate covered with a transmission electron microscope grid in saturated relative humidity. A two-level microporous hybrid film with a block copolymer skeleton formed on the substrate after evaporation of the organic solvent and water. One level of order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…7c). The decoration of TiO 2 NPs on pore walls can be ascribed to the famous Pickering emulsion effect 31 , which prefers driving nanoparticles to be selectively absorbed at the water/solution interface for the stabilization of water droplets during the BF process 32 . When the same casting solution was coated on the fabric by conventional method in ambient conditions, no porous microstructures are observed on the surface of fabric (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7c). The decoration of TiO 2 NPs on pore walls can be ascribed to the famous Pickering emulsion effect 31 , which prefers driving nanoparticles to be selectively absorbed at the water/solution interface for the stabilization of water droplets during the BF process 32 . When the same casting solution was coated on the fabric by conventional method in ambient conditions, no porous microstructures are observed on the surface of fabric (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, after completely volatilization of solvent and water, a honeycomb sequence alignment structure is formed on the polymer membranes. As the formation of the porous films were influenced by several parameters including relative humidity (R.H.), temperature, solvent, the structure and component of polymers and polymer concentration, and so forth. In this work, the effects of solvent, temperature, molecular weight, and polymer concentration were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…microstructures, [38] which can be used to engineer PPMs if one of the BCP blocks is ap olyelectrolyte.A ss uch, av ariety of BCPs consisting of an eutral hydrophobic polystyrene (PS) block and an ionic hydrophilic block (e.g.P AA [37] and P4VP [39] )w ere investigated. Ma and co-workers reported that the hydrophilicity of the PA Ablock was essential to form porous PS-b-PAA films with better regularities and larger pores.…”
Section: Block Copolymer (Bcp) Porous Polyelectrolyte Membranesmentioning
confidence: 99%